2019
DOI: 10.1016/j.redox.2018.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Ascorbate attenuates red light mediated vasodilation: Potential role of S-nitrosothiols

Abstract: There is significant therapeutic advantage of nitric oxide synthase (NOS) independent nitric oxide (NO) production in maladies where endothelium, and thereby NOS, is dysfunctional. Electromagnetic radiation in the red and near infrared region has been shown to stimulate NOS-independent but NO-dependent vasodilation, and thereby has significant therapeutic potential. We have recently shown that red light induces acute vasodilatation in the pre-constricted murine facial artery via the release of an endothelium d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 43 publications
2
19
0
Order By: Relevance
“…R/NIR stimulated vasodilation was previously tested with the mouse facial artery, a surrogate for microvascular function. Consistent with previous observations, there was a 14.2% (±0.81) increase in vessel diameter after 5 min of light exposure to pre-constricted facial arteries ( Fig 1A ) [ 16 , 17 ]. Since potassium channels are key mediators of vasodilation, we tested the impact of channel inhibition on NIR vasodilation.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…R/NIR stimulated vasodilation was previously tested with the mouse facial artery, a surrogate for microvascular function. Consistent with previous observations, there was a 14.2% (±0.81) increase in vessel diameter after 5 min of light exposure to pre-constricted facial arteries ( Fig 1A ) [ 16 , 17 ]. Since potassium channels are key mediators of vasodilation, we tested the impact of channel inhibition on NIR vasodilation.…”
Section: Resultssupporting
confidence: 92%
“…The effect plateaued when light was removed and then increased upon re-stimulation with light. There was no significant difference in the magnitude of R/NIR vasodilation in femoral vessels when compared to the facial artery in Fig 1 or previously published observations [ 16 , 17 ]. Patch clamp K + channel current recording from freshly dissociated mouse femoral arterial muscle cells using symmetrical K + (145 mM) recording solutions revealed existence of a 273 pS single K + channel current that displayed voltage-dependent increased openings and sensitivity to inhibition by the selective large conductance Ca 2+ -activated K + channel (BK Ca ) antagonist paxilline (1 μM) ( Fig 3A–3C ).…”
Section: Resultssupporting
confidence: 66%
See 2 more Smart Citations
“…In our previous studies, we found that targeting the downregulation of GTP-cyclohydrolase 1 caused by IR to prevent endothelial dysfunction could be a new strategy for the prevention of RE (Yan et al, 2020). Gch1 is the rate-limiting enzyme in the synthesis of tetrahydrobiopterin, the content of which plays an important role in maintaining endothelial NOS function, producing NO and maintaining vasodilation (Douglas et al, 2018b;Keszler et al, 2019). However, there is a lack of drugs that can improve this reduction in Gch1 observed after IR.…”
Section: Introductionmentioning
confidence: 99%